E-modules with Android Appy Pie Based on Socio-Scientific Issues to Improve Students' Critical Thinking Skills - Sulistiani, Sulistiani; Kartimi, Kartimi; Sahrir, Dede Cahyati (Universitas Pendidikan Ganesha, 2022)
Learning is limited and not maximized in the use of technology in every school. In addition, learning that is still focused on the teacher as a learning resource, causes students to be less critical in understanding the existing problems, so that technology is needed, with the application of socio-scientific issue-based E-modules. The purpose of this study is to determine the effect of implementing E-modules based on socio-scientific issues in improving students' critical thinking skills. The method used in this research is quantitative research with a quasi-experimental approach. The research design used a pretest-posttest control group design, with class X MIPA 1 as the experimental class and class X MIPA 4 as the control class. The results showed that there was an increase in students' critical thinking skills in the experimental class which was higher than the control class with the average difference between the pretest and posttest results in the control class. This increase can be seen from the statistical paired samples as significant output. The results of the student response questionnaire showed a good category. The conclusion in this study is that the application of E-modules using android appy pie based on socio-scientific issues has an effect on increasing students' critical thinking skills.